Kesesuaian Kualitas Air Irigasi untuk Padi Sawah di Daerah Irigasi Mambal - I GUSTI NGURAH SANTOSA; I PUTU DHARMA (Fakultas Pertanian Universitas Udayana, 2019)
Suitability of Irrigation Water Quality for Rice in Mambal Irrigation Area. Mambal irrigation area is located in southern region of Bali, close by urban area. It consists of 42 Subak which covered 4.820 ha. However, the total area that still exists today is only 2.978 ha, and it is considered potential in increasing rice production and supplying rice in order to support food self-sufficiency in Bali. The increase of population is considered as the factor of wetland conversion because, the growth of population leads to variety of purposes such as shelter (housing), tourism/hotel, accommodation, business/home industry, livestock, public facilities, etc. Therefore, the activities done on the wetland conversion area automatically changed. That activity on conversion area consequences in both liquid or solid waste, and it is often discharged into rivers or irrigation channels. Consequently, it may cause irrigation water pollution. Poor quality of irrigation water can endangering rice plant growth and reduce the production, which means blocking or inhibiting food self-sufficiency. This study is considered as field and laboratory research. There are some field activities done, namely observation of the pollution sources and types of pollutants, as well as waste disposal mechanisms and technologies used to tackle pollution. In order to determine the quality of irrigation water, the water samples taken in the primary channel (1 water sample), secondary channel (1 water sample), tertiary channel (1 water sample), and field area (3 samples of water). All water samples are analyzed at the Analytical Laboratory of Udayana University. The results of the study are the sources of pollution come from channel natural environments, public facilities, housing and household waste. It was found that there are some types of waste, namely natural garbage, artificial garbage, liquid or solid waste in small amount. The mechanism of waste disposal is done conventionally and there is no application of technology of waste disposal. The outcome of the study is irrigation water quality for rice is still suitable for irrigation.